2015
DOI: 10.1148/radiol.15142062
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coronary Artery Calcification and Mortality in the National Lung Screening Trial: A Comparison of Three Scoring Methods

Abstract: Purpose To evaluate three coronary artery calcification (CAC) scoring methods to assess risk of coronary heart disease (CHD) death and all-cause mortality in National Lung Screening Trial (NLST) participants across levels of CAC scores. Materials and Methods The NLST was approved by the institutional review board at each participating institution, and informed consent was obtained from all participants. Image review was HIPAA compliant. Five cardiothoracic radiologists evaluated 1575 low-dose computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
235
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(257 citation statements)
references
References 24 publications
6
235
0
5
Order By: Relevance
“…69 For the second ordinal method, 0 ¼ very low risk, 1e5 ¼ mildly increased risk, 6e11 ¼ moderately increased risk, and 12e30 ¼ moderate to severely increased risk. 68 For visual assessment analysis, none ¼ very low risk, mild ¼ mildly increased risk, moderate ¼ moderately increased risk, and severe ¼ moderately to severely increased risk. 68 Treatment recommendations should parallel the risk classification and are particularly critical in this context since the referring physicians have not requested the CAC scores and are not likely to be familiar with the therapeutic algorithms for each CAC level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…69 For the second ordinal method, 0 ¼ very low risk, 1e5 ¼ mildly increased risk, 6e11 ¼ moderately increased risk, and 12e30 ¼ moderate to severely increased risk. 68 For visual assessment analysis, none ¼ very low risk, mild ¼ mildly increased risk, moderate ¼ moderately increased risk, and severe ¼ moderately to severely increased risk. 68 Treatment recommendations should parallel the risk classification and are particularly critical in this context since the referring physicians have not requested the CAC scores and are not likely to be familiar with the therapeutic algorithms for each CAC level.…”
Section: Discussionmentioning
confidence: 99%
“…68 For visual assessment analysis, none ¼ very low risk, mild ¼ mildly increased risk, moderate ¼ moderately increased risk, and severe ¼ moderately to severely increased risk. 68 Treatment recommendations should parallel the risk classification and are particularly critical in this context since the referring physicians have not requested the CAC scores and are not likely to be familiar with the therapeutic algorithms for each CAC level. Formal treatment recommendations, however, are beyond the scope of this guideline; they may be part of forthcoming SCCT Expert Consensus and other documents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dutch and Italian lung cancer CT screening trials have reported the ability of non-cardiacgated chest CT to detect coronary artery disease. [24][25][26] Chiles et al 27 have shown that a global assessment of the volume of calcified coronary artery plaque in smokers undergoing noncardiac-gated chest CTs can help risk stratify patients for coronary heart disease associated mortality. However, there is no evidence that standard axial chest CT has the ability to detect cardiomyopathies per se, and we could not find another published series with which to compare our results too.…”
Section: Discussionmentioning
confidence: 99%